The impact of Bophuthatswana's independence on the geographical landscape of Thaba Nchu - Selosesha - Kwaw, Isaac Wilson (University of the Free State, 1994)
This study focuses on the impact of Bophuthatswana's independence as a political process on the geographical landscape of Thaba Nchu-Selosesha from a political geographical perspective in the period from 1976 to 1992. In spite of a lack of international acceptance of Bophu thatswana' s independence, independence as a political process is a fact that cannot be disputed. From the time of the country's inception, a number of strategies and policies were instituted to meet the aspirations of the people. These strategies and polices include the following: * the process of nation-building and fostering unity among the fragmented blocks of land which constituted Bophuthatswana; * to promote industrial development at a given centre supported by industrial incentives to attract local and foreign investors which aim to develop the economic potential of those centres; * to establish district administrative centres; * to stimulate housing development; * to promote educational development; * to improve health development; and * to promote the development of recreational, culture and tourism facilities. This research attempts to unveil the spatial manifestation of the implementation of the strategies and policies on the geographical landscape of Thaba Nchu-Selosesha from 1976 to 1992. The overall objectives of the research include the following: * to review the literature on the impact of political process on land-use patterns, and to identify process models which have been used for political geographical analysis; * to examine the pre-independent political processes and to give a description of the pre-independent geographical landscape of Thaba Nchu-Selosesha as in 1976; * to analyze independence as a political and socioeconomic process associated with the transformation of the pre-independence geographical landscape of Thaba Nchu-Selosesha from 1977 to 1992; * to serve as a stock-taking of the landscape patterns created by independence as Bophuthatswana enters a new political dispensation resulting from the country's re-incorporation into a democratic South Africa; * to provide scenarios of possible changes in the geographical landscape of Thaba Nchu-Selosesha in a changing South Africa; and * to contribute to the knowledge and understanding of the impact of independence as a political process on landscape patterns. In trying to achieve the above objectives, the research placed the study area in the context of the pre-independent geographical landscape and its salient morphological features were identified as a basis for assessing the impact of independence as a political process. The aerial photographs of the study area for 1976 and 1992 were extrapolated on a scale of 1:50 000 and the former was superimposed on the latter to identify expansion and new land-use patterns which have emerged in the study area. In addition, horizontal photographs were taken of the visible evidence of changes which cannot be discerned on the 1992 map. The landscape components studied included the following: political, administrative, settlement, housing, commercial, industrial, cultural, recreational and tourism, and health. educational, The ultimate findings about the spatial manifestation of the impact of independence as a political process after fifteen years indicated that the physical structures, forms and functioning of Thaba Nchu-Selosesha had undergone a tremendous transformation. If an assessment is made of the changes in the landscape of Thaba Nchu-Selosesha from 1976 to 1992 it appears that all ten landscape components being analyzed had been transformed as a result of Bophuthatswana's political independence as a changing political process. The political landscape was transformed from a South African homeland, together with the adjacent white town (Thaba Nchu) landscape into a unique landscape, typical of Bophuthatswana national ism. The administrative infrastructure was transformed into a district administrative center for the Thaba Nchu district as a whole. The amalgamation of the Selosesha Town Council with the Thaba Nchu Municipal Council merged the two boundaries and a new urban boundary was drawn. The settlement landscape had been moulded during the pre-independent era into two distinct settlement patterns, viz. formal urban (Selosesha and Thaba Nchu) and informal settlements (African rural villages and the Bultfonteins), including the squatter settlement of Kromdraai. Since independence the most major transformation of the settlement landscape was: the evacuation of Kromdraai squatter settlement in 1979; the political, administrative, and spatial amalgamation of the Thaba Nchu and Selosesha towns; the expansion of Selosesha towards Unit 1, the emergence of an elite suburb north of Thaba Nchu town; and the continuation of an informal housing sprawl in the informal settlements where some ad hoc upgrading of individual housing units materialized. The industrial landscape only emerged after independence when Thaba Nchu-Selosesha was proclaimed as an Industrial Development Point within Bophuthatswana's space economy. Industrial development was not only the largest financial injection which Thaba Nchu received from the national government since independence but is also caused the greatest scale of landscape transformation in the study area. The commercial landscape did not only expand towards Selosesha and the surrounding informal settlements, but the original CBD of Thaba Nchu town is virtually unrecognisable as new buildings were erected to replace the old ones. Infrastructural development, in a spatially integrated planning approach to unite the Thaba Nchu Shopping Centre at Selosesha with Thaba Nchu's CBD, was undertaken. The educational landscape was expanded as a result of the construction of a number of new educational facilities (of which the Thaba Nchu College of Education and the Manpower Training Centre are the most prominent), as well as the upgrading and relocation of educational facilities. The health landscape was transformed by the establishment of a larger and more sophisticated variety of health facilities. The cultural landscape came to be dominated by the Mmabana Cultural Centre in the CBD, while the tourist landscape emerged with the building of the Naledi Sun. It is thus clear that a large variety of types and scales of landscape transformations occurred in Thaba Nchu-Selosesha as a result of the political independence of Bophuthatswana in 1977 of which the settlement, industrial, commercial, and educational landscape transformations are the most prominent. At the same time, new landscapes, e.g. political, administrative, industrial, commercial, educational, cultural, and tour ism emerged. There are instances where the pre-independent physical patterns remained e.g. formal and informal settlements and formal and informal housing. In conclusion, a process model has been proposed by which the changing geographical landscape of Thaba Nchu-Selosesha can be explained.
Keywords: Homelands (South Africa) -- Politics and government; Bophuthatswana -- History; Bophuthatswana (Thaba 'Nchu) -- Politics and government; Dissertation (M.A. (Geography))--University of the Free State, 1994